Total fenolik dan aktivitas antioksidan formula susu kecambah kedelai dan ekstrak beras hitam terenkapsulasi dengan variasi jenis penyalut - Siti Aminah; Wikanastri Hersoelistyorini; Agus Suyanto; Nurrahman Nurrahman; Ali Rosidi; Wulandari Meikawati; Diode Yonata (AGROINTEK, 2022)
Soybean sprouts and black rice have bioactive components that are beneficial for health. Both of these ingredients can be developed as functional drink ingredients. Encapsulation is one method to maintain bioactive components. This study aims to determine the total phenol content and antioxidant activity of the formula of soy sprouted milk (SKK): encapsulated black rice extract (EBH) (F1: SKK 100 %: EBH 0 %; F2: SKK 75 %: EBH 25 %; F3: SKK 50 %: EBH 50 %; F4: SKK 25 %: EBH 75 %; F4: SKK 0 %: EBH 100 %), with various coating materials: maltodextrin (MDE), Arabic gum (GA) and a mixture of MDE:GA (MGA). The results showed that the highest total phenol was obtained at F5, of all coatings: MDE (85.06 mg GAE/kg); GA (84.27 mg GAE/kg); MGA (82.49 mg GAE/kg). The highest antioxidant activity was obtained in the F3 treatment, with GA coating (58.009 % RSA). It is known that there is a tendency to increase total phenolic, in the formulation of higher concentrations of EBH. In general, MGA combined coating materials produced higher mean total phenols than MDE and GA alone. There was no tendency to increase antioxidant activity in either the formula or the type of coating